Young Girls, Little Science and Full Dreams - González Chávez, Daniela Fernanda; Núñez Arzola, Axel; Núñez San Miguel, Itzcoatl; Méndez-Rodríguez, Arantza; Torres Perea, Cecilia Guadalupe; Delgado, Héctor; Serrano, Miguel Ángel; Regules, Álvaro (My University, 2021)
Mexico is a leading country in young dreamers, with great capacity to get involved in the aerospace sector and all the disciplines that may come from it; unfortunately it is also an entity where adults mostly underestimate the generations that are their successors, although they too have been denied the opportunity to exploit their potential in any area. At STEAM DREAMERS Aguascalientes we verify this obstacle from primary education, until students are forced to choose a professional career, even with the few tools to do so. STEAM DREAMERS Aguascalientes is a scientific dissemination group made up of young people passionate about science who seek to promote love towards it and make known that women have great potential in this field, since the leaders of the same are 17-year-old girls, whose greatest purpose is to distribute information and develop the skills of the participants in the programs and events offered by the group, from a very simple perspective so that anyone who has not had an approach to it before, that when they start considering a university career, take into account what they are passionate about and how you can use it to collaborate in the environment where you live. We know that we live in a technological era, but we omit the shortcomings of young people in being able to understand and handle it, in addition to few virtuous of their knowledge they cannot share their ideas in a correct way and at the moment of sharing it with the people; STEAM DREAMERS is an excellent means to cultivate young people in creativity and fluid exposition of ideas, the enthusiasm that we apply to visual and audiovisual material on our platforms, allows us to focus the appropriate information on students from elementary to high school. The group has 5 strategies to implement science in the student community: Seminars, talks, ideathons, information capsules and technology workshops. These categories ensure that we have a critical thinking society that starts at an early age. Currently the project is the only one of its kind in the state of Aguascalientes, but we hope to be the cradle of those fure scientists who will improve the world, and be an inspiration for the generations to come. Copyright © 2021 by the International Astronautical Federation (IAF). All rights reserved.